A Legal Review Of The Differences In Handling Drug Abusers And Drug Dealers : Case Study Number 456/PID.SUS/2025/PN SRG - Juan Carlos Marbun; M. Nassir Agustiawan; Mohammad Hifni (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
This study aims to analyze the judges' considerations in distinguishing between the two categories of offenders, evaluate the conformity of the verdicts with applicable legal principles and provisions, and identify obstacles in the implementation of rehabilitation for drug abusers and law enforcement against drug dealers. This study is a normative legal study using a case study method on Serang District Court Decision Number 456/Pid.Sus/2025/PN.Srg, which tried two defendants in one case: a 17-year-old student (drug user) and a 32-year-old adult male (drug dealer). The results of the study show that the panel of judges comprehensively applied the principles of substantive justice and individualization of punishment. The judges considered legal and non-legal factors holistically, such as motive, psychological examination results, evidence of transactions, and potential for rehabilitation. Defendant A (the user) was sentenced to 1 year in prison with the provision of rehabilitation, in accordance with Article 54 of the Narcotics Law, while Defendant B (the dealer) was sentenced to 12 years in prison without remission, in accordance with Article 114 paragraph (1) of the Narcotics Law. This verdict is consistent with the principles of legality, proportionality, and restorative justice. However, the study also revealed obstacles in the implementation of rehabilitation, such as limited facilities at the National Narcotics Agency (BNN), a lack of integration in the referral system, and a lack of coordination between agencies